A Bottom-up Network Slicing Procedure in F-RAN. Issue 1 (February 2020) - Wang, Tao; Zhu, Zhaopeng; Hu, Yu
Abstract: As a core technology of future mobile communication networks, network slicing can provide users with end-to-end, customized, and isolated network connections. Thereby it is of great significance for improving network resource utilization and improving user experience. F-RAN, as a solution for 5G access network, has features such as low latency, support of mobility, and content awareness. Through the analysis of traditional network slicing control and service management and combined with the distributed computing and cache capabilities provided by the F-RAN architecture, this paper proposes a new type of network slice process. Different from traditional network slicing procedure, such procedure can respond to delay-sensitive services and reduce the fronthaul network load, and it could be used as a solution for network slicing in the F-RAN architecture.